Investigation model of sensing, seizing and reconfiguring capabilities - Patrício, V.; Lopes da Costa, R.; Carvalho, H.; Pereira, L.; Dias, Á.; Gonçalves, R. (International Journal of Value Chain Management, 2022)
The dynamic capabilities view came to life as an enhancement of the resource based-view (RBV) and became the most prolific research stream of the resource-based approaches, with most critics pinpointing definitional issues, contradictory interpretations, and tautological assumptions as issues to solve before the view could become a theory. This research lays its foundations in the creation of a model which has the fundamental constructs of sensing, seizing and reconfiguring capabilities complemented by exploration and exploitation concepts of organisational ambidexterity constructs. To assess the applicability of this model a qualitative approach method is used by applying 21 semi-structured interviews in Portugal. The outcome of these interviews presented a set of capabilities that companies should attempt to properly sense, seize and reconfigure to develop dynamic capabilities. The main contribution to the field of strategy is a proposal of an investigation model that suggests a link between the two constructs of sensing/seizing, and exploration/exploitation.